HIGH VALUED LIMONENE IN ESSENTIAL OIL EXTRACT FROM LIME PEEL WASTE FOR PARFUM INDUSTRY - Rosdanelli Hasibuan; Rita Sundari; Elisabeth Gultom; Rini Anggraini; Juliza Hidayati (AGROINTEK, 2021)
Limonene in essential oils is highly valuable attracts great interest of consumers due to its specific fragrance. It is not surprising that many big perfume industries are looking for high purified limonene found in essential oils of certain fruits and flowers. This study investigates the extraction process of essential oil from lime peel waste. This study has used two extraction methods, i.e.  maceration method and Soxhlet technique. Two types of organic solvent applied, i.e. hexane and ethanol. This work studies the effect of extraction time, type of organic solvent, and extraction method on yield of extraction. Characterization studies as FTIR (Fourier Transform Infra Red) Spectroscopy related to type of chemical bonding of limonene in essential oil and GC-MS (Gas Chromatography – Mass Spectrometry) related to limonene fragmentation have also investigated.